Recalibrating the compass: towards effective competition law enforcement on mixed markets - Jasper P. Sluijs (Market and Competition Law Review)
The undertaking, a cornerstone of EU competition law, has consistently been approached as a functional concept. Any entity engaged in economic activity should be considered an undertaking, thereby ensuring consistent application of competition law across competitors. However, current national enforcement practice reveals a departure from the functional approach to the undertaking on mixed markets, where public and private firms compete. Particularly, allegedly anticompetitive behaviour by public entities has evaded competition law scrutiny in the Netherlands, because competition law was found not to apply to these public entities. Drawing on a jointly interpreted string of CJEU cases in competition law and state aid law – which this article coins as the “Compass doctrine” – the Dutch competition authority and courts found that economic activity by public entities is exempt from competition law when connected to the exercise of public power. Analysis of the Compass doctrine cases reveals how a number of case-specific outcomes taken together have allowed for an undermining of the functional approach to the undertaking. It is demonstrated how the sum of the Compass doctrine is larger than its individual parts, which seems to have been unforeseen by the CJEU. This article demonstrates how the Compass doctrine has two adverse consequences: (1) because it undermines the functional approach to the undertaking as the subject of competition law, it impedes effective enforcement; (2) the Compass doctrine enables public firms to behave anticompetitively on mixed markets. The CJEU never anticipated the advent of commercial behaviour by public entities, who with the Compass doctrine in hand can infringe competition law with impunity. Experiences in the Netherlands to this effect should be regarded as a canary in the coal mine for mixed markets across the EU. Therefore, it is incumbent on the CJEU to revisit the Compass doctrine in future cases, which may follow from preliminary references. This article recommends the CJEU to (re)emphasize that once an entity is engaged in economic activity, it can no longer escape competition law scrutiny by being connected to the exercise of public authority. To protect the level playing field on mixed markets, all economic activity should explicitly be subject to EU competition law.